IMPLICATIONS OF ECONOMIC AND SOCIAL INEQUALITY ON COMMUNITY WELFARE: A LITERATURE REVIEW - Setyo Gunawan; Al-Amin (Adisam Publisher, 2025)
This study aims to explore the impact of economic and social inequality on people's welfare through a comprehensive literature review. Economic and social inequality is an increasingly prominent issue in many countries and has far-reaching implications for societal stability and development. This study identifies that high inequality contributes to various social problems such as increased crime, declining public health, and limited access to education and economic opportunities. In addition, inequality weakens social cohesion and trust among community members, which can impact political stability and the effectiveness of public policies. To address these negative impacts, this study suggests the need for fairer redistributive policies, as well as improved access to fundamental services such as education and health, to improve individual well-being and achieve more inclusive and sustainable economic growth.